Self‐Assembled Perovskite Nanoislands on CH3NH3PbI3 Cuboid Single Crystals by Energetic Surface Engineering (Adv. Funct. Mater. 50/2021). (8th December 2021) - Zhang, Yurou; Kim, Dohyung; Yun, Jung‐Ho; Lim, Jongchul; Jung, Min‐Cherl; Wen, Xiaoming; Seidel, Jan; Choi, Eunyoung; Xiao, Mu; Qiu, Tengfei; Lyu, Miaoqiang; Han, EQ; et al.
Abstract : Self‐Assembled Perovskite Nanoislands In article number 2105542, Jung‐Ho Yun, Jae Sung Yun, Lianzhou Wang, and co‐workers report an energetic surface engineering strategy to restructure non‐uniform CH3 NH3 PbI3 perovskite crystal surfaces. By thermally evaporating energetic CsI on single crystal surfaces, a unique nano‐island structure is formed through a cation interdiffusion process. This morphology induces a gradient band bending, which increases the charge carrier mobility by 60.